PENGARUH BUDAYA ORGANISASI, KOMPETENSI, DAN MOTIVASI KERJA TERHADAP KINERJA TENAGA PENDIDIK (GADIK) DI PUSDIK INTELIJEN POLRI - Gede Putra Muliawan (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2022)
The purpose of this research was to determine the effect organization culture, competency, and work motivation toward performance of educator. The research was conducted using quantitative opprocach. The population in this study were 205 educators at the Pusdik Intelijen Polri. Selected sample by using simple random sampling technique as much as 51 educators. The data obtained with questionnaires and analyzed using multiple regression model and path analysis. The result of this research finding show that organization culture, competency, and work motivation have positive direct effect toward performance. Organizational culture, competence, and work motivation simultaneously have a positive effect of 86,7% on the educator’s performance. Partialy, organizational culture has positive effect of 36,4% on the educator’s performance, competence has positive effect of 32,1% on the educator’s performance, and work motivation has a positive effect of 18,2% on the educator’s performance. Based on the results of this reseacrh, performance of educators at Pusdik Intelijen Polri can be improved by increasing the strength of organizational culture, competence, and work motivation. Keywords: performance, motivation, competency